The Children's Somatic Symptoms Inventory-8: Psychometric Properties of a Brief Measure of Somatic Distress - Amanda L. Stone; Judy Garber; Lynn S. Walker (MDPI AG, 2024)
Background: Children often present to primary and specialty care clinics with multiple somatic symptoms of nonspecific origin that can be highly distressing and prompt significant health service use. We evaluated the psychometric properties of the eight-item Children's Somatic Symptoms Inventory (CSSI-8) as a brief measure of somatic distress that could be easily integrated into clinical systems. Method: Eight items from the 24-item CSSI were selected based on their representation of multiple bodily systems, association with high base rates, and ability to maximize the separation of the items' Rasch measure scores. The psychometric quality of the eight-item scale was evaluated in 876 pediatric patients with chronic abdominal pain and a nonclinical sample of 954 school children using methods from three psychometric models (the classical test theory, Rasch modeling, and confirmatory factor analysis). Results: The CSSI-8 showed good measurement properties on an extensive array of psychometric criteria, had adequate Rasch person separation reliability for a brief instrument (rsep = 0.74-0.75), and distinguished between clinical and nonclinical youth. Girls in both groups had significantly higher CSSI-8 scores than boys. Norms for the clinical sample are presented. Conclusions: The CSSI-8 is a psychometrically sound measure suitable for use as a brief dimensional assessment of pediatric somatic distress.